The dynamic constitution: An introduction to American constitutional law - Fallon, Richard H (Cambridge University, 2013)
In this book Harvard law professor Richard H. Fallon, Jr., introduces nonlawyers to the workings of American Constitutional Law. He writes about leading constitutional doctrines and issues, including the freedom of speech, the freedom of religion, the guarantee of equal protection, rights to fair procedures, and rights to privacy and sexual autonomy. Along the way, Fallon describes many of the fascinating cases and personalities that have shaped constitutional law. He shows how historical, cultural, and other factors have influenced constitutional adjudication, making clear the dynamic nature of the Constitution.